Green Accounting Perspective on Sustainability Development Goals - Rifai, Achmad; Ramadhan, Yanuar (Universitas Negeri Semarang, 2024)
Purpose: The study is conducted to determine the factors that affect sustainable development goals (SDGs) in Indonesia listed companies with a green accounting approach. Three independent variables (ESG disclosure, environmental performance, and green accounting) were empirically tested to determine their relationships with sustainable development goals (SDGs). Method: The data set covers 16 companies that are consistently listed on the Jakarta Islamic Index (JII) during the period 2020 - 2024, data source was collected with purposive sampling technique, and hypotheses were tested using an ordinary least square regression random effect model. Findings: The results showed that ESG disclosure, environmental performance, and green accounting simultaneously affect sustainable development goals. Partially, ESG disclosure and environmental performance have a significant positive effect on sustainable development goals, while green accounting has no effect on sustainable development goals. Novelty: This study brings us to a different point of view, explaining that achieving sustainable development goals from a green accounting perspective. According to the findings, stakeholders can use it in making business decisions, both by companies and governments. Further research can add the variable of company value to see the investor’s perspective in contribute achieving sustainable development goals.